A frameshift mutation in the cubilin gene (CUBN) in Beagles with Imerslund–Gräsbeck syndrome (selective cobalamin malabsorption). (27th October 2013) - Drögemüller, Michaela; Jagannathan, Vidhya; Howard, Judith; Bruggmann, Rémy; Drögemüller, Cord; Ruetten, Maja; Leeb, Tosso; Kook, Peter H.
Summary Mammals are unable to synthesize cobalamin or vitamin B12 and rely on the uptake of dietary cobalamin. The cubam receptor expressed on the intestinal endothelium is required for the uptake of cobalamin from the gut. Cubam is composed of two protein subunits, amnionless and cubilin, which are encoded by the AMN and CUBN genes respectively. Loss‐of‐function mutations in either the AMN or the CUBN gene lead to hereditary selective cobalamin malabsorption or Imerslund–Gräsbeck syndrome (IGS). We investigated Beagles with IGS and resequenced the whole genome of one affected Beagle at 15× coverage. The analysis of the AMN and CUBN candidate genes revealed a homozygous deletion of a single cytosine in exon 8 of the CUBN gene (c.786delC). This deletion leads to a frameshift and early premature stop codon (p.Asp262Glufs*47) and is, thus, predicted to represent a complete loss‐of‐function allele. We tested three IGS‐affected and 89 control Beagles and found perfect association between the IGS phenotype and the CUBN:c.786delC variant. Given the known role of cubilin in cobalamin transport, which has been firmly established in humans and dogs, our data strongly suggest that the CUBN:c.786delC variant is causing IGS in the investigated Beagles.